An Investigation of Students’ Ability to Understand Digital Article on Social Platforms - Sari Eka Nurindah; Mareta Rae Shella Tivani; Erniati Erniati (English Literature Study Program, Faculty of Humanities, Diponegoro University, 2025)
AbstractThis research was conducted by taking the theme of digital literacy. This research aimed to evaluate how does students’ digital literacy level affect their ability to critically understand and retell digital articles shared on social media platforms and investigate the factors contributing to students’ difficulties in understanding digital articles on social platforms. Specifically, it seeks to explore digital literacy, cognitive processing, linguistic comprehension, and social media dynamics interact to affect students’ ability to interpret and evaluate digital article critically.This research was conducted using a descriptive quantitative research method. The subjects of this research were students of English Education Department. The research instruments used to collect data were questionnaires to investigate the factors contributing to students’ difficulties in understanding digital articles on social platforms and tests to evaluate how does students’ digital literacy level affect their ability to critically understand and retell digital articles shared on social media platforms. The sampling method used in this study is the total sampling method.The result of the research indicated that the ability to critically understand and retell digital articles shared on social media platforms of English Education Students ranged from good to very poor, with the majority falling into the fair to poor category (17,983). Meanwhile, the factors contributing to students’ difficulties in understanding digital articles on social platforms were attributed to several factors. First, students were not accustomed to read digital articles on social platforms. Second, they struggled with numerous unfamiliar words and sentence structures, particularly in digital article on social platforms texts.